Working Together for Learning Together: Supporting Students and Teachers with Collaborative Instruction - Shamberger, Cynthia Thrasher; Friend, Marilyn (Journal of the American Academy of Special Education Professionals, 2013)
Professional educators are called upon to provide effective instruction to student populations that increasingly consist of multiple cultures, languages, and ethnic backgrounds. Based on current special education law, schools are working toward establishing more collaborative cultures by stressing partnerships between general and special education teachers, which often includes initiating inclusive practices such as co-teaching. This article reviews the professional literature regarding the inception of inclusive practices and the factors that influenced this concept in the field. Particularly, skills for collaboration and the practice of co-teaching are examined in the context of the developing trend toward more collaborative interactions in school setting.